FRA ROCKER TIL AKADEMIKER - Mørck, Line Lerche (Psyke & Logos, 2015)
The article is a product of collaboration between a researcher (Line) and a former biker gang member (Peter). Together they explore Peter’s conduct in life during a 10-month period, while he is in a police-gang-exit-program. The article reflects and discusses the ethics involved in this kind of subject/subject research, where a former biker gang member and a researcher are engaged in a common research process, being both researchers and subject of investigation at the same time. Through a social practice theoretical moment-movement methodology significant moments are studied in depth, including Peter’s action reasons, (disturbances of) concerns and telos becoming less of a member of the (biker) gang environment and becoming more of a member of academia. The article further explores the struggles to move beyond marginal positions and how collective processes of recognition and reification might help major personal changes. Finally the article discusses possibilities for development within the field of gang exit intervention - to improve gang exit processes for other future gang members.